Within-treatment changes in a novel addiction treatment program using traditional Amazonian medicine - David M. O'Shaughnessy; Ilana Berlowitz; Robin Rodd; Zoltán Sarnyai; Frances Quirk (SAGE Publishing, 2021)
Aims: The therapeutic use of psychedelics is regaining scientific momentum, but similarly psychoactive ethnobotanical substances have a long history of medical (and other) uses in indigenous contexts. Here we aimed to evaluate patient outcomes in a residential addiction treatment center that employs a novel combination of Western and traditional Amazonian methods. Methods: The study was observational, with repeated measures applied throughout treatment. All tests were administered in the center, which is located in Tarapoto, Peru. Data were collected between 2014 and 2015, and the study sample consisted of 36 male inpatients who were motivated to seek treatment and who entered into treatment voluntarily. Around 58% of the sample was from South America, 28% from Europe, and the remaining 14% from North America. We primarily employed repeated measures on a psychological test battery administered throughout treatment, measuring perceived stress, craving frequency, mental illness symptoms, spiritual well-being, and physical and emotional health. Addiction severity was measured on intake, and neuropsychological performance was assessed in a subsample from intake to at least 2 months into treatment. Results: Statistically significant and clinically positive changes were found across all repeated measures. These changes appeared early in the treatment and were maintained over time. Significant improvements were also found for neuropsychological functioning. Conclusion: These results provide evidence for treatment safety in a highly novel addiction treatment setting, while also suggesting positive therapeutic effects.